Impact of nanoclay on physicomechanical and thermal analysis of polyvinyl alcohol/fumed silica/clay nanocomposites - Lai, J.C-H.; Rahman, M.R.; Sinin, Hamdan; Liew, F.K.; Rahman, M.M.; Hossen, M.F. (John Wiley and Sons Inc., 2015)
Polyvinyl alcohol (PVA)/fumed silica/clay nanocomposites are prepared via solution intercalation by exploiting phase separation based on the bridging of particles by polymer chains. PVA/fumed silica/clay nanocomposites are characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy, and thermogravimetric analysis. Mechanical properties are determined by universal testing machine. From FTIR results, it indicates that IR spectrum for PVA/fumed silica/clay nanocomposites, especially PVA/fumed silica/clay (1.30E) nanocomposites, is much broader than pure PVA and other clay nanocomposites. The better interfacial bonding between PVA/fumed silica/clay (1.30E) nanocomposites are reflected in the improvement of the mechanical properties as well as thermal stability. The surface area analysis result proves that the PVA/fumed silica/clay (1.30E) nanocomposites have higher surface area and pore volume with less pore size. With the addition of 1.30E clay to the composite system, the tensile strength and modulus had shown the highest values as well as higher activation energy for thermal decomposition.